(untitled) (Foro de Educacion, 2019)
The main objective of that article is to understand how to use free softwares as methodological tools for chemistry teaching within Redenção´s council public schools, in Ceará – Brazil state, from the teachers and students point of view. Asking them what are the main challenges experienced by the teachers and high school students about chemistry teaching with the use of free softwares andhow would be the experience of knowledge mediation through free softwares. Using the qualitative approach with a research-action study with five teachers and eighteen high school students, it was verified that the teaching and learning of Chemistry in the state school system of Redenção used the computer lab, but did not work with software. The main difficulties pointed by teachers for not using them were: technology lack of control with free softwares, Linux/Ubuntu operating systems limits; softwares in foreign language, softwares´ limits, and lack of knowledge of software for chemistry teaching use. Both students and teachers believe in free softwares use viability to turn the teaching-learning more interactive, more contextualized, and more concrete, and show interest to use those methodological tools, especially states of matter, concentrations and build your molecule softwares.